Lile
Lile
02-10-2014
Mathematics
contestada
Which equation is equivalent to y-6=-12(x+4)
Respuesta :
macio06
macio06
02-10-2014
We can simplify equation to find equivalent.
y-6=-12(x+4) (now just multiplying factor -12 by each argument in the parenthesis.
y-6=-12x-48 /+6 add both side
y=-12x-42
Every form above is equivalent to given equation but the last is the simplest.
Answer Link
scarab21
scarab21
02-10-2014
The equations is equivalent to y = -12x - 42
Answer Link
VER TODAS LAS RESPUESTAS ( 43+ )
Otras preguntas
Which of the following is the equation of a line parallel to the line y=3x+2, passing through the point (10,1)? A. 3x - y=29 B. 3x + y=29 C. -3x - y=29 D. 3x +
one way in whick Robespierre and Louis XVI of France are similar is that both
Hello how do you solve for x a= x-b/y
Carla's plant was 10 2/3 inches tall. Yolanda's was 8 3/4 inches tall. How much taller was Carla's plant than Yolanda's?I came up with 2 11/12. Am I right??
what is the fraction ten twelfths in it's simplest form ?
what did Benjamin franklin feel strong about
A microscope is set so it makes an object appear 4 x 10`2 times larger than its actual size. A virus has a diameter of of 2 x 10`-7 meter. how large will the di
How do you find the length of a circle in geometry?
What is the last number
solve for x₁ and x₂6x₁+3x₂=606x₁-2x₂=80